Spontaneous Middle Cerebral Artery MCA dissection and stenosis: role of vessel wall imaging and 3D-RA endoluminal view as adjunct diagnostic tools in endovascular therapy - Kamis, Mohd Fandi Al Khafiz; Mohd Yaakob, Mohd Naim; Abdul Rahim, Ezamin; Muda, Ahmad Sobri; Md Noh, Mohamad Syafeeq Faeez (Elsevier, 2021)
Intracranial dissection has a wide spectrum of clinical presentation from causing intracranial hemorrhage to steno-occlusive ischemia. Anterior intracranial circulation is an uncommon site for dissection. Multimodality imaging is required before deciding on the best treatment for each patient. We present a case of left middle cerebral artery dissection causing steno-occlusive ischemia and hypoperfusion. This case demonstrates how MRI vessel wall imaging and endoluminal view of three-dimensional rotational angiogram as an adjunct tool to help us diagnosed and achieve optimum endovascular therapy for our patients.